Person-centred care for dementia patients (backend and frontend system) student #2 - Lim, Alexander Hong Xun (Nanyang Technological University, 2021)
Dementia is a syndrome which deteriorates one’s cognitive abilities beyond the expected rate of normal ageing. Patients with dementia may be impaired in certain brain activities such as memory, thinking and problem solving. To assist them, the person-centred care strategy has been adopted worldwide. Person-centred care is an essential component of high-quality dementia care which includes several key elements such as treating people as individuals, valuing patients and their caregivers, and creating a positive social environment. It involves a close collaboration between the patients, caregivers, care centres and healthcare providers to express their knowledge and opinions to develop a comprehensive care plan for the recovery of the patients. In this project, an application known as Person-centres Care (PEAR) system will be developed to assist the care centre’s staffs and provide higher quality care for patients with dementia. This platform will serve as a centralized system to facilitate communication between the different stakeholders which include the supervisor, game therapist, caregiver, administrator, and guardian. This system consists of a web application and a mobile application which provide different sets of functionalities based on the user operating the system. The objective of the project is to maintain and enhance features to the inherited PEAR android mobile application as a front-end developer. The mobile application should consider the following principles which include performance, user experience, consistency, correctness and quality. The main tasks of the project include code and User Interface reviews to fix inconsistencies and bugs found in the mobile application. In addition, proper documentation and test cases should be developed to complement the 3 changes made to the code. Guidelines on the workflow for the frontend team will also be documented. Furthermore, as the backend team is transitioning to a new backend system, the (Application Programming Interfaces) APIs were updated. The frontend team must accommodate to the changes and migrate to the new API system. The final product of the project is to deliver an improved and functional android mobile application.